Liability in BIM projects—Preliminary review results. (June 2022) - Taghizadeh, Katayoun; Yavari Roushan, Tayebe; Alizadeh, Maryam
Building Information Modelling (BIM) fosters a collaborative working environment. With the industry moving toward this change, most practitioners believe that, compared to traditional methods, there will be a change in project liabilities and risk assignment. Design integration through BIM leads to ambiguity in determining the party responsible for the design. Therefore, BIM parties need to understand not only BIM but also the change in their responsibilities and think of solutions to liability and risk assignment. Based on the information gathered from three resources, this study aims at reviewing solutions to design liability assignment. These three resources are as follows: the existing research studies in the field of BIM adoption challenges, the existing contractual standards such as AIA G202, and contract conditions of 10 BIM projects. Findings indicate that there has been a lack of attention to design liability in BIM. The results provide significant insights into the status of BIM liability issue, the existing gaps in the knowledge, and potential future research.